2008
DOI: 10.1038/sj.clpt.6100453
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Warfarin Dosage Requirements Based on CYP2C9 and VKORC1 Genotypes

Abstract: Polymorphisms in CYP2C9 and VKORC1 have been shown to be associated with warfarin dose requirements and could be used to predict warfarin dose. We conducted a prospective study in which warfarin dose was prescribed based on CYP2C9 and VKORC1 polymorphisms in 108 Han-Chinese patients without prior warfarin treatments. Using the genotype-based dosing, 83% of patients reached stable, therapeutic international normalized ratio (INR) within 2 weeks of treatment initiation and none of the patients developed clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
99
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 42 publications
9
99
0
1
Order By: Relevance
“…White people show considerable variability in CYP2C9, whereas people of African and Asian descent are predominantly of the CYP2C9*1*1 genotype, predisposing them to normal warfarin metabolism. White people and people of African descent have greater allelic diversity of VKORC1; those of Asian descent are predominantly of the VKORC1AA genotype, 76 the allelic type associated with increased sensitivity to warfarin; and those of African descent are predominantly of the VKORC1BB genotype, the allelic type associated with decreased sensitivity to warfarin. Thus, polymorphisms in CYP2C9 have a larger effect on warfarin dose in white people, whereas VKORC1 polymorphisms affect warfarin dose in white people and people of African and Asian descent, with highest prevalence in those of Asian descent.…”
Section: Discussionmentioning
confidence: 99%
“…White people show considerable variability in CYP2C9, whereas people of African and Asian descent are predominantly of the CYP2C9*1*1 genotype, predisposing them to normal warfarin metabolism. White people and people of African descent have greater allelic diversity of VKORC1; those of Asian descent are predominantly of the VKORC1AA genotype, 76 the allelic type associated with increased sensitivity to warfarin; and those of African descent are predominantly of the VKORC1BB genotype, the allelic type associated with decreased sensitivity to warfarin. Thus, polymorphisms in CYP2C9 have a larger effect on warfarin dose in white people, whereas VKORC1 polymorphisms affect warfarin dose in white people and people of African and Asian descent, with highest prevalence in those of Asian descent.…”
Section: Discussionmentioning
confidence: 99%
“…6 This inter-individual variability is known to be affected not only by environmental factor, but also by genetic influence. 5,7 Candidate-gene association studies have identified two genes responsible for the main proportion of the genetic effect: CYP2C9, which codes for the enzyme cytochrome P450 2C9 that metabolizes S-warfarin, and VKORC1, which codes for warfarin's target, vitamin K epoxide reductase. 8 Several single nucleotide polymorphisms (SNPs) in VKORC1 have been associated with a deficiency in vitamin-K dependent clotting factors, resulting in either increased sensitivity to w-arfarin or warfarin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5). [111][112][113][114] Warfarin is a VKA. It is completely absorbed orally, and 98% to 99% is bound to plasma proteins.…”
Section: Food and Drug Interactionsmentioning
confidence: 99%